Distinguishing pancreatic cancer and autoimmune pancreatitis with in vivo tomoelastography - Zhu, Liang; Guo, Jing; Jin, Zhengyu; Xue, Huadan; Dai, Menghua; Zhang, Wen; Sun, Zhaoyong; Xu, Jia; Marticorena Garcia, Stephan R.; Asbach, Patrick; Hamm, Bernd; Sack, Ingolf (European radiology, 2021)
Objectives To prospectively investigate the stiffness and fluidity of pancreatic ductal adenocarcinoma (PDAC) and autoimmune pancreatitis (AIP) with tomoelastography, and to evaluate its diagnostic performance in distinguishing the two entities. Methods Tomoelastography provided high-resolution maps of shear wave speed ( c in m/s) and phase angle ( φ in rad), allowing mechanical characterization of the stiffness and fluidity properties of the pancreas. Forty patients with untreated PDAC and 33 patients with untreated AIP who underwent diagnostic pancreatic MRI at 3-T together with multifrequency MR elastography and tomoelastography data processing were prospectively enrolled. Ten healthy volunteers served as controls. Two radiologists and a technician measured pancreatic stiffness and fluidity independently. The two radiologists also independently evaluated the patients’ conventional MR sequences using the following diagnostic score: 1, definitely PDAC; 2, probably PDAC; 3, indeterminate; 4, probably AIP; and 5, definitely AIP. Interobserver agreement was assessed. Stiffness and fluidity of PDAC, AIP, and healthy pancreas, as well as diagnostic performance of tomoelastography and conventional MRI, were compared. Results AIP showed significantly lower stiffness and fluidity than PDAC and significantly higher stiffness and fluidity than healthy pancreas. Pancreatic fluidity was not influenced by secondary obstructive changes. The intraclass correlation coefficient for pancreatic stiffness and fluidity by the 3 readers was near-perfect (0.951–0.979, all p < 0.001). Both stiffness and fluidity allowed distinguishing PDAC from AIP. AUCs were 0.906 for stiffness, 0.872 for fluidity, and 0.842 for conventional MRI. Conclusions Pancreatic stiffness and fluidity both allow differentiation of PDAC and AIP with high accuracy. Key Points • AIP showed significantly lower stiffness and fluidity than PDAC and significantly higher stiffness and fluidity than healthy pancreas. • Both stiffness and fluidity allowed distinguishing PDAC from AIP. • Pancreatic fluidity could distinguish malignancy from non-malignant secondary obstructive changes.